PENGARUH POSTUR MOTIVASI DITINJAU DARI COMMITMENT, CAPITULATION, RESISTANCE, DISENGAGEMENT DAN GAME PLAYING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Taufik, Agus (Universitas Islam Negeri Sunan Kudus, 2016)
This research aims to find out the influence of motivation postur and education level to the personal obligation tax loyalt of report SPT. Sampling of this research as many as 66 personal obligation tax who has small industrial.The Multiple regressionanalytic show upof motivation postur consist of capitulation, resistance, disengagement and game playing, also education level doesn‟t influence partialy of report SPT. However commitment give as partial influence personal obligation tax loyalty of report SPT. But, simultanly all of variable didn‟t influence the personal obligation tax loyalty ofreport SPT.